Human capital formation, inequality and competition for job (2007)
This paper develops a model where heterogeneous agents compete for the best available jobs. Firms, operating with different technologies, rank job candidates in the human capital dimension and hire the best available candidate due to complementarities between the worker¿s human capital and technologies used in the production process. As a result, individuals care about their relative ranking in the distribution of human capital because this determines the firm they will be matched with and therefore the wage they will receive in equilibrium. The paper rationalizes a different channel through which peer effects and human capital externalities might work: competition between individuals for the best available jobs (or prizes associated with the relative position of individuals). We show that more inequality in the distribution of endowments negatively affects aggregate efficiency in human capital formation as it weakens competition for jobs between individuals. However, we find that the opposite is true for wage inequality, namely, more wage inequality encourages competition and, as a result, agents exert more effort and accumulate more human capital in equilibrium.